A heat treatment method for high wear-resistant bulk high entropy alloy, high entropy alloy obtained by the method and application thereof
Through vacuum arc smelting and heat treatment processes, the structural structure of high-entropy alloys is optimized, and the problems of complex heat treatment processes and insufficient performance improvement of high-entropy alloys in the existing technology are solved, and high-entropy alloy materials with high strength, plastic toughness and wear resistance are realized.
Patent Information
- Application Number
- CN202310324235.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-30
AI Technical Summary
The existing high-entropy alloy heat treatment process is complex, and the process parameters have a great impact on the alloy performance, resulting in the inability to fully improve the strength, plastic toughness and wear resistance of the alloy, and the cutting processing performance is not excellent.
The high-entropy alloy ingot is prepared by vacuum arc smelting technology. After the heat treatment process of tempering, hot forging and cold rolling, the structural structure of the alloy is optimized and its strength, plastic toughness and wear resistance are improved.
Through this method, the segregation of the obtained high-entropy alloy components is weakened, the component distribution is more uniform, the hardness and wear resistance are improved by 2 to 3 times, and the cutting processing performance is also significantly improved.
Smart Images

Figure CN116356223B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high entropy alloy preparation, processing and heat treatment, and specifically relates to a heat treatment method for a high wear-resistant block high entropy alloy, a high entropy alloy obtained by the method and applications thereof. Background Art
[0002] Metal alloys are widely used materials in industrial production and play an indispensable role in life and production. However, the mechanical properties of alloys after solution treatment cannot meet the actual engineering requirements to a certain extent. Therefore, the application of alloys after solution treatment is greatly limited, making it a general trend to further improve the mechanical properties of alloy materials such as strength and plasticity. This is conducive to improving the quality of metal alloy materials and improving the utilization rate of alloy materials in industrial production.
[0003] In recent years, high entropy alloys, as a new type of alloy, have shown better mechanical properties than traditional metals due to their special four effects that greatly hinder dislocation movement. However, there are still few studies on the evolution of alloy microstructures during heat treatment of high entropy alloys, so the evolution law of related alloy microstructures is not clear, which makes the microstructure and properties of high entropy alloys obtained by heat treatment extremely random.
[0004] Patented technology of "Ultrasound and pressure integrated assisted high entropy alloy heat treatment technology" (CN109457197A), the molecular formula of the high entropy alloy is AlCoCrFeNiTi 0.5 . The heat treatment process of this technology includes: fixing the high entropy alloy with a pressure that does not cause plastic deformation of the sample, placing the sample in an 800°C heat treatment furnace, ensuring an argon atmosphere and starting an ultrasonic environment, keeping warm for 5 hours, and cooling with the furnace. The present invention effectively realizes the transformation of high entropy alloy grains, refines its grain structure, and improves its comprehensive mechanical properties. Although this technology has an effect of improving the comprehensive mechanical properties of high entropy alloys, the process flow is relatively long and the process parameters involved in each process have a greater impact on the alloy properties, which is not conducive to actual operation and control.
[0005] Patented technology of "A high entropy alloy shock heat treatment technology" (CN110106457A), the molecular formula of the high entropy alloy is AlCoCr 0.5 FeNiTi 0.5 . The heat treatment process of this technology includes: heating the sample, heat preservation, mechanical pulse impact, controlled speed cooling, heat preservation, furnace cooling, and obtaining the workpiece. The present invention ultimately refines the high entropy alloy grains, eliminates casting defects, and improves the comprehensive performance of the material by adjusting various process parameters. Although this technology has an improvement effect on the comprehensive mechanical properties of high entropy alloys, the process flow is long and the process parameters involved in each process have a great influence on the alloy performance, which is not conducive to actual operation and control.
[0006] There are many existing high entropy alloy heat treatment processes. For example, the hardness and wear resistance of the high entropy alloy after heat treatment in "A heat treatment method for NbMoTaW series refractory high entropy alloy" (CN113817971A) are improved by 0.5 to 1 times, but this heat treatment process is relatively complex, the heat treatment time is long, and it is not combined with forging technology, so that the processed alloy has poor cutting processability. The heat-treated high entropy alloy of the present invention combines forging and rolling processes to improve the hardness and wear resistance of the alloy, and improve the cutting processability of the alloy. Summary of the invention
[0007] In order to solve the shortcomings of the prior art and optimize the organizational structure of the produced high entropy alloy, the present invention provides a heat treatment method for a high wear-resistant block high entropy alloy, a high entropy alloy obtained by the method and its application. The heat treatment method adopted by the present invention includes alloy treatment processes of tempering, hot forging and cold rolling of the high entropy alloy, which can obtain an alloy material with high strength, high plasticity and good comprehensive mechanical properties.
[0008] The technical solution provided by the present invention is as follows:
[0009] A method for heat treating a high wear-resistant bulk high entropy alloy comprises the following steps:
[0010] 1) High entropy alloy ingots are prepared by vacuum arc melting technology, i.e. high entropy alloy after solid solution treatment, and the prepared high entropy alloy ingots are cut into cuboids with the dimensions of 25-30 cm in length, 25-30 cm in width and 30-35 cm in height respectively;
[0011] 2) subjecting the high entropy alloy ingot obtained in step 1) to a tempering treatment:
[0012] 201) Quenching treatment: heating the high entropy alloy ingot to 950-1150° C. and keeping the temperature for 80-120 min, and then cooling it to room temperature in the furnace;
[0013] 202) High temperature tempering treatment: heating the high entropy alloy ingot to 500-650° C., keeping the temperature for 60-90 min, and cooling with the furnace;
[0014] 3) hot forging the high entropy alloy obtained in step 2) at a temperature of 900 to 1100° C., with a final forging thickness of 20 to 28 mm, and cooling at room temperature;
[0015] 4) rolling the high entropy alloy hot forging billet obtained in step 3) at room temperature, with a pass reduction of 15 to 25 mm and a total reduction rate of ≥ 75%, to obtain a high wear-resistant block high entropy alloy, i.e., a heat-treated high entropy alloy;
[0016] Wherein, in step 1), the chemical composition and corresponding mass percentage of the high entropy alloy ingot are: Ti: 10.5-12.5wt.%, B: 0.5-1.5wt.%, Cr: 21.5-23.5wt.%, Ni: 38-40wt.%, Al: 0-12.5wt.%, and the rest are Fe and some unavoidable impurities, wherein 10≤Ti+B≤15 (wt.%), 55≤Cr+Ni≤65 (wt.%), 0.5≤Fe / Ti≤2.5 (mass percentage ratio), and the total mass percentage of each component is 100%.
[0017] The above technical solution:
[0018] The high entropy alloy used has better strength, plasticity, toughness and wear resistance.
[0019] After the above-mentioned heat treatment including tempering, hot forging and cold rolling, compared with the high-entropy alloy directly obtained after solid solution treatment, the component segregation of the heat-treated high-entropy alloy is weakened, the component distribution is more uniform, and it has better strength, plasticity, toughness and wear resistance.
[0020] Based on the above technical solution, a high entropy alloy cold-rolled sheet with a thickness of 3 to 5 mm is obtained. The present invention avoids the occurrence of high entropy alloy segregation after solution treatment through repeated smelting technology, and makes the high entropy alloy have good strength and plastic toughness through heat treatment process, eliminates the residual stress inside the alloy, improves the alloy cutting performance, obtains a crystal structure with uniform composition and finer than conventional steel, and the hardness and wear resistance of the alloy after heat treatment are 2 to 3 times higher than those after solution treatment.
[0021] Specifically, in step 1): raw materials with a purity of ≥99.99% are used as raw materials for the high entropy alloy ingot.
[0022] Furthermore, in step 1), the high entropy alloy ingot is first polished using 600# to 800# sandpaper to remove the oxide layer on the surface of the ingot, and then cut;
[0023] Specifically, in step 1), the high entropy alloy ingot is prepared according to its chemical composition and content, smelted in a vacuum arc melting furnace, then placed in a mold for forming, and the obtained high entropy alloy casting is heated and solution treated to obtain the high entropy alloy ingot.
[0024] The conditions for melting in the vacuum arc melting furnace are as follows:
[0025] Vacuum the furnace (2~10)×10 -3 Pa, and discharged from bottom to top in the order of Al, Ni, Fe, Ti, Cr, and B;
[0026] The smelting current is 200-500A, the smelting time is 40-200min, and the smelting is repeated at least 3 times.
[0027] The conditions of the heating solution treatment are as follows: the solution treatment is carried out in a high temperature oxidation furnace at 600 to 1500° C. for 60 to 180 minutes.
[0028] Furthermore, in step 3), the high entropy alloy ingot is firstly polished with 600# and 800# sandpaper, and then hot forging is performed.
[0029] Specifically, in step 4): in the rolling step, the final rolling thickness of the cold-rolled sheet is 3 to 5 mm.
[0030] The present invention also provides a high wear resistant block high entropy alloy prepared according to the above-mentioned high wear resistant block high entropy alloy heat treatment method.
[0031] The present invention also provides an application of the above-mentioned high wear-resistant blocky high entropy alloy for preparing high wear-resistant cutting tools and molds.
[0032] Further, the obtained high entropy alloy cold-rolled sheet is subjected to the following steps:
[0033] 5) Cut the high entropy alloy cold-rolled plate to a size of (30-60)×(20-80)×(20-40) (mm).
[0034] 6) Conduct microscopic observation on the microstructure of the high entropy alloy samples after cutting.
[0035] Step 6) Before metallographic observation, each metal surface needs to be polished with 400-1500# sandpaper until the scratches are in the same direction, and the polished high entropy alloy is polished with a polishing paste with a particle size of 1.5-3 μm.
[0036] Step 6) The polished sample is micro-etched with 3-6% nitric acid alcohol until the alloy surface changes color slightly, then it can be washed off with alcohol and blown dry.
[0037] The beneficial effects of the present invention are:
[0038] 1) Compared with traditional alloys or high entropy alloys, it has better strength, plasticity, toughness and wear resistance.
[0039] 2) Compared with the high entropy alloy after solution treatment, the component segregation of the heat-treated high entropy alloy is weakened, the component distribution is more uniform, and it has better strength, plasticity, toughness and wear resistance.
[0040] 3) The comprehensive mechanical properties are excellent, and the difference in mechanical properties along the thickness direction of the steel plate is small and uniform; the internal quality of the steel plate is excellent, and there are no defects in the flaw detection.
[0041] 4) The characteristics of the elements themselves have a positive effect on improving the performance of the alloy:
[0042] Ti: Titanium is a high melting point element. In the process of alloy bonding, it is located in the middle transition zone of the periodic table, so it is easy to form an interstitial solid solution structure with the alloy. Under the effect of solid solution strengthening, it can improve the comprehensive mechanical properties of the alloy to a certain extent. In addition, titanium has the effect of refining the grain structure of the alloy, and the fine and dense structure formed has a positive effect on improving the strength and toughness of the alloy. During the wear process, the titanium element is easily oxidized to form an oxide film, which plays a role of lubrication and protection during the friction process, thereby achieving the effect of reducing the wear rate of the alloy.
[0043] B: Boron can be used as a modifier in the alloy system to refine the grains, reduce the melting point, reduce expansion, and improve the strength, hardness, and wear resistance of the alloy. In addition, boron has a certain purification effect on the alloy smelting process, which can greatly reduce the accumulation of impurity atoms at the grain boundaries, reduce the width of the grain boundaries, and reduce the barrier effect of the grain boundaries on dislocations, thereby improving the smelting effect of the alloy.
[0044] Cr: Chromium is the main element for high temperature oxidation resistance in common alloy systems. Due to its high melting point, it generates Cr2O3 or chromium-containing spinel structure during wear and heating, and forms a dense and continuous oxide layer, blocking further contact between gas and alloy matrix, and improving the material's high temperature oxidation resistance. In addition, chromium is a strong carbide-forming element, which can form a large amount of Cr 23 C6 and other carbides can effectively improve the wear resistance of the alloy. A higher chromium content can enhance the hardenability of the alloy, making the alloy less prone to cracking under extreme working conditions such as rapid cooling and heating, thereby extending the service life. Too high a chromium content increases production costs, so the chromium content of the present invention is 21.5-23.5wt.%, which ensures that the prepared high entropy alloy has good practicality in a hot and cold alternating working environment, including excellent high temperature oxidation resistance and good wear resistance.
[0045] Ni: Nickel is a hard, ductile and ferromagnetic metal that is highly polishable and corrosion-resistant. Nickel is an iron-loving element and is easily combined with iron in the alloy system to increase the hardness of the alloy. Nickel is insoluble in water and forms a dense oxide film on the surface in humid air at room temperature, which can prevent the main metal from further oxidation and improve the wear resistance of the alloy surface.
[0046] Al: Aluminum itself has an FCC structure, but it is also an element that promotes the formation of BCC phase in the high entropy alloy system. Adding an appropriate amount of aluminum makes the BCC phase structure of the alloy system account for a larger proportion, improving the overall strength, hardness and wear resistance of the alloy. Aluminum has a significant regulatory effect on the performance of dual-phase high entropy alloys, promoting the formation of a bidirectional structure inside the alloy with better performance than the unidirectional structure. Aluminum is a light metal element with an atomic radius of 0.143nm. Adding aluminum can distort the original lattice structure, reduce the free energy of the system, and play a role in solid solution strengthening. At the same time, aluminum can also form a dense oxide film on the surface of the alloy, improving the alloy's resistance to high-temperature oxidation and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 1 is a metallographic diagram of the high entropy alloy after solution treatment in Example 1.
[0048] Figure 2 It is the metallographic phase diagram of the heat-treated high entropy alloy in Example 1.
[0049] Figure 3 This is the metallographic phase diagram of the high entropy alloy after solution treatment in Example 2.
[0050] Figure 4 This is the metallographic phase diagram of the heat-treated high-entropy alloy in Example 2.
[0051] Figure 5-6 They are the SEM morphology pictures of Example 1 after solution treatment and heat treatment.
[0052] Figure 7-8 They are the SEM morphology pictures of Example 2 after solution treatment and heat treatment. DETAILED DESCRIPTION
[0053] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0054] Example 1
[0055] Obtaining aluminum-free high wear resistant bulk high entropy alloy by heat treatment method of high wear resistant bulk high entropy alloy
[0056] The preparation method of this embodiment is:
[0057] The raw materials are Fe, Ti, B, Cr, Ni, and Al spherical metal elements with a purity of not less than 99.99%, and the ingredients are prepared according to the following mass percentages: 10.5wt.% Ti, 0.5wt.% B, 21.5wt.% Cr, 38wt.% Ni, 0wt.% Al, and 29.5wt.% Fe. Before preparing the ingredients, the surface of the raw materials is first polished with 600# and 800# sandpaper to remove foreign matter and metal oxides on the surface, and then ultrasonically cleaned in water and alcohol. After cleaning, it is dried at 80°C for 2 hours, and the raw materials are retained for use. Use a vacuum arc melting furnace for high-temperature melting, take out the remaining metal raw materials, and put a certain amount of metal raw materials into the water-cooled copper crucible of the arc melting furnace in the order of B, Cr, Ti, Fe, and Ni. First, evacuate the vacuum. When the vacuum degree reaches below 2.5×10-3Pa, fill it with inert gas to -0.04MPa for alloy melting. The arc is 250A and the melting current is 500A. After the melting is completed, the ingot is turned over after rapid water cooling. After repeated melting for 3 times, a high-entropy alloy ingot with uniform internal structure and high wear resistance is obtained. After the melting is completed, it is cooled in a water-cooled copper crucible to obtain a high-entropy alloy material ingot. Subsequently, the cooled alloy ingot is placed in a high-temperature oxidation furnace at 800℃ for solution treatment for 80min. After completion, the alloy is oil quenched to obtain a high-entropy alloy after solution treatment.
[0058] Cutting of heat treatment experimental samples: Use wire cutting equipment to cut the ingot material into 25mm×25mm×35mm heat treatment patterns. Place the cut heat treatment patterns in a quenching furnace, and control the heating rate of the quenching furnace to 10℃ / min, heat to 1000℃, and keep warm for 100min after heating treatment.
[0059] Cooling treatment: After the heat preservation treatment, the high entropy alloy heat-treated sample is immediately air-cooled (cooled to room temperature).
[0060] The alloy sample after quenching and cooling was placed in a tempering furnace, and the heating rate of the tempering furnace was controlled to be 10°C / min, and the temperature was raised to 600°C. After the heating treatment, the temperature was kept for 80 minutes to make the sample composition more uniform.
[0061] The samples after tempering treatment are hot forged. Before hot forging, the samples need to be polished with 600# and 800# sandpaper in turn to remove the oxide film on the metal surface, and the hot forging heating rate is controlled to 10℃ / min, and the temperature is raised to 1000℃ to ensure that the thickness of the samples after hot forging treatment is 25mm.
[0062] The samples after heat treatment and hot forging were cut and cold rolled according to the rolling size of the cold rolling mill. The thickness of the cold rolled plate was 5 mm, the pass reduction was 20 mm, and the total reduction rate was 80%, thereby obtaining a heat-treated high entropy alloy.
[0063] The metallographic images of the high entropy alloy after solution treatment and final heat treatment were observed, and the wear resistance (wear quality) was measured. The grains are denser and the wear resistance is 1.3 times higher than that after solution treatment. The test steps of wear resistance are as follows: the prepared samples are subjected to sliding friction and wear tests (Bruker, UMT3, USA wear test prototype), stainless steel is selected as the grinding material, the load is 30N, the working temperature is room temperature, the wear time is 30min, the alloy wear mode can be rotation or reciprocating linear motion, the rotation speed is 200r / min, and the reciprocating speed is 0.1m / s.
[0064] The hardness value of Example 1 measured by a Vickers hardness tester is 802 HV1.
[0065] Example 2
[0066] Aluminum-containing high wear-resistant bulk high entropy alloy is obtained by heat treatment of high wear-resistant bulk high entropy alloy
[0067] The chemical composition and mass percentage of the high entropy alloy in Example 2 are 12.5wt.%Ti, 1.5wt.%B, 23.5wt.%Cr, 40wt.%Ni, 12.5wt.%Al, 10wt.%Fe, and the preparation, heat treatment steps and test methods are the same as those in Example 1, except that Al is added to the high entropy alloy composition used in Example 1. The test results show that the wear resistance of the heat-treated high entropy alloy is 1.6 times higher than that after solution treatment.
[0068] The hardness value of Example 1 measured by a Vickers hardness tester is 834 HV1.
[0069] By comparison Figure 1 and Figure 2 It can be seen that the grains of the heat-treated high-entropy alloy are finer and more uniform than those of the solution-treated high-entropy alloy, and the distribution is more dispersed. The number of refined grains is significantly increased, and the clustered structure area is significantly reduced.
[0070] By comparison Figure 3 and Figure 4 It can also be seen that the grains of the heat-treated high-entropy alloy are finer and more uniform than those of the solution-treated high-entropy alloy, and the distribution is more dispersed. The number of refined grains is significantly increased, and the clustered structure area is significantly reduced.
[0071] By comparison Figure 5-Figure 6It can be seen that a large number of scratches and fine particles appear on the surface of the high-entropy alloy after solution treatment, and the wear mechanism is abrasive wear; the scratches of the high-entropy alloy after heat treatment are relatively reduced and a large number of oxidized debris appear on the surface. The wear mechanism is the coexistence of abrasive wear and oxidative wear. The oxide film formed in the oxidative wear process inhibits the intensification of the wear behavior of the alloy surface and has a certain protective effect on the alloy.
[0072] By comparison Figure 7-Figure 8 It can be seen that after wear, trace scratches and large hard particles appear on the surface of the high-entropy alloy treated with solid solution, and the wear mechanism is abrasive wear; the scratches on the high-entropy alloy after heat treatment are relatively reduced and a large number of oxide flake structures appear on the surface. The wear mechanism is the coexistence of abrasive wear and oxidative wear. The oxide film formed in the oxidative wear process inhibits the intensification of the wear behavior of the alloy surface and has a certain protective effect on the alloy.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A heat treatment method for a high wear-resistant bulk high entropy alloy, characterized in that: The following steps are involved: 1) According to the chemical composition and content of the high entropy alloy ingot, the high entropy alloy ingot is melted in a vacuum arc melting furnace, then placed in a mold for forming, and the obtained high entropy alloy casting is subjected to heating and solid solution treatment to obtain the high entropy alloy ingot, wherein the conditions of the heating and solid solution treatment range are: solid solution treatment in a high temperature oxidation furnace at 600 to 1500° C. for 60 to 180 minutes; and the prepared high entropy alloy ingot is cut into a cuboid with the length, width and height of 25 to 30 cm; 25 to 30 cm; 30 to 35 cm respectively; 2) subjecting the high entropy alloy ingot obtained in step 1) to a tempering treatment: 201) Quenching treatment: heating the high entropy alloy ingot to 950-1150° C. and keeping the temperature for 80-120 min, and then cooling it to room temperature in the furnace; 202) High temperature tempering treatment: heating the high entropy alloy ingot to 500-650° C., keeping the temperature for 60-90 min, and cooling with the furnace; 3) hot forging the high entropy alloy obtained in step 2) at a temperature of 900 to 1100° C., with a final forging thickness of 20 to 28 mm, and cooling at room temperature; 4) rolling the high entropy alloy hot forging billet obtained in step 3) at room temperature, with a pass reduction of 15 to 25 mm and a total reduction rate of ≥ 75%, to obtain a high wear-resistant block high entropy alloy; Wherein, in step 1), the chemical composition and corresponding mass percentage of the high entropy alloy ingot are: Ti: 10.5-12.5wt.%, B: 0.5-1.5wt.%, Cr: 21.5-23.5wt.%, Ni: 38-40wt.%, Al: 0-12.5wt.%, and the rest are Fe and some unavoidable impurities, wherein 10≤Ti+B≤15 (wt.%), 55≤Cr+Ni≤65 (wt.%), 0.5≤Fe / Ti≤2.5, and the total mass percentage of each component is 100%.
2. The heat treatment method for a high wear-resistant bulk high entropy alloy according to claim 1, characterized in that: In step 1), raw materials with a purity of ≥99.99% are used as raw materials for the high entropy alloy ingot.
3. The heat treatment method for a high wear-resistant bulk high entropy alloy according to claim 1, characterized in that: In step 4): in the rolling step, the final rolling thickness of the cold-rolled sheet is 30 to 50 mm.
4. The heat treatment method for a high wear-resistant bulk high entropy alloy according to claim 1, characterized in that: In step 1), the high entropy alloy ingot is first polished with 600# to 800# sandpaper to remove the oxide layer on the surface of the ingot, and then cut; In step 3), the high entropy alloy ingot is firstly polished with 600# and 800# sandpaper, and then hot forging is performed.
5. The heat treatment method for a high wear-resistant bulk high entropy alloy according to claim 1, characterized in that: The conditions for melting in the vacuum arc melting furnace are as follows: Vacuum the furnace (2~10)×10 -3 Pa, and discharged from bottom to top in the order of Al, Ni, Fe, Ti, Cr, and B; The smelting current is 200-500A, the smelting time is 40-200min, and the smelting is repeated at least 3 times.
6. A high wear resistant bulk high entropy alloy prepared according to the high wear resistant bulk high entropy alloy heat treatment method according to any one of claims 1 to 5.
7. The use of the high wear-resistant bulk high entropy alloy according to claim 6, characterized in that: Used for making highly wear-resistant knives and moulds.
Citation Information
Patent Citations
Ultrasound and pressure integrated assisting thermal treatment technique for high-entropy alloy
CN109457197A
High-entropy alloy impact heat treatment process
CN110106457A
Heat treatment method of NbMoTaW series refractory high-entropy alloy
CN113817971A
Method for improving strength of single-phase high-entropy alloy by combining heat treatment with plastic deformation
CN107083527A
Preparation method of high-strength and high-plasticity aluminum-iron-chromium-nickel high-entropy alloy
CN113564442A